Сhallenges of the modern model of formation and implementation of the Russian state innovation policy - A. N. Gusarova; D. Yu. Znamenskiy (Управление)
The state innovation policy of modern Russia has been analyzed in the article. The problems of the existing model of formation and implementation of the state innovation policy have been considered. This direction of policy has been studied from the standpoint of institutional, technological and time components, which allows us to characterize the modern model of the state innovation policy of Russia as a model implemented “top-down”, as the center of decision-making was shifted towards the state in the face of government agencies and decision-makers with minimal consideration of the views of other stakeholders. The subject of this study is the interaction of political institutions in the formation and implementation of the state innovation policy of Russia. The role of small and medium-sized enterprises of scientific, technical and innovative orientation in the studied processes as the most “sensitive” market needs has been emphasized, the focus has been shifted to increase the responsibility of the first persons of the regions for regional innovative development, as well as to the nominal nature of the state priority of innovative development of Russia. As a methodological basis, a system-dynamic approach is used, which allows you to reveal systematically the shortcomings of the current system, expressed in the limited interaction of political institutions, their communication and the quality of partnerships. This is largely due to the symbolic (nominal) political demand for such development and the weak setting, optimal for the development of innovation, socio-political environment. The conclusion has been made, that it is possible to correct the current state of affairs when changing: the legal support of the innovation sphere, the subject composition of the participants in the development and implementation of state policy in the field of innovation and the conditions for the development and growth of innovation.